The Ṁ–M* relation of pre-main-sequence stars: a consequence of X-ray driven disc evolution. Issue 1 (31st January 2014) - Ercolano, B.; Mayr, D.; Owen, J. E.; Rosotti, G.; Manara, C. F.
ABSTRACT: We analyse current measurements of accretion rates on to pre-main-sequence stars as a function of stellar mass, and conclude that the steep dependence of accretion rates on stellar mass is real and not driven by selection/detection threshold, as has been previously feared. These conclusions are reached by means of statistical tests including a survival analysis which can account for upper limits. The power-law slope of the Ṁ–M* relation is found to be in the range of 1.6–1.9 for young stars with masses lower than 1 Mȯ . The measured slopes and distributions can be easily reproduced by means of a simple disc model which includes viscous accretion and X-ray photoevaporation. We conclude that the Ṁ–M* relation in pre-main-sequence stars bears the signature of disc dispersal by X-ray photoevaporation, suggesting that the relation is a straightforward consequence of disc physics rather than an imprint of initial conditions.